Few-cycle, broadband, mid-infrared optical parametric oscillator pumped by a 20-fs Ti:sapphire laser - Chaitanya Kumar, Suddapalli (Laser Photon Rev, 2014)
A few-cycle, broadband, singly-resonant optical parametric oscillator (OPO) for the mid-infrared based on MgO-doped periodically-poled LiNbO(3) (MgO:PPLN), synchronously pumped by a 20-fs Ti:sapphire laser is reported. By using crystal interaction lengths as short as 250 µm, and careful dispersion management of input pump pulses and the OPO resonator, near-transform-limited, few-cycle idler pulses tunable across the mid-infrared have been generated, with as few as 3.7 optical cycles at 2682 nm. The OPO can be continuously tuned over 2179-3732 nm (4589-2680 cm(-1)) by cavity delay tuning, providing up to 33 mW of output power at 3723 nm. The idler spectra exhibit stable broadband profiles with bandwidths spanning over 422 nm (FWHM) recorded at 3732 nm. The effect of crystal length on spectral bandwidth and pulse duration is investigated at a fixed wavelength, confirming near-transform-limited idler pulses for all grating interaction lengths. By locking the repetition frequency of the pump laser to a radio-frequency reference, and without active stabilization of the OPO cavity length, an idler power stability better than 1.6% rms over >2.75 hours is obtained when operating at maximum output power, in excellent spatial beam quality with TEM(00) mode profile. Photograph shows a multigrating MgO:PPLN crystal used as a nonlinear gain medium in the few-cycle femtosecond mid-IR OPO. The visible light is the result of non-phase-matched sum-frequency mixing between the interacting beams.